Charge Transfer Metal‐Organic Framework Containing Redox‐Active TTF/NDI Units for Highly Efficient Near‐Infrared Photothermal Conversion - Yan, Tong; Li, Yu‐Yang; Su, Jian; Wang, Hai‐Ying; Zuo, Jing‐Lin (Chemistry : a European journal, 2021)
Metal‐organic frameworks (MOFs), as a class of new inorganic‐organic hybrid crystal materials, could have important applications in near‐infrared (NIR) photothermal conversion. Herein, a new charge‐transfer MOF (Co‐MOF) with mixed ligands of H4TTFTB and bpmNDI incorporating redox‐active tetrathiafulvalene/naphthalene diimide (TTF/NDI) units into one system is reported. Due to the presence of TTF/NDI oxidative and reductive couples, stable radicals can be observed in the MOF. In addition, charge transfer from the electron donor (TTF) to the acceptor (NDI) results in a broad absorption in the NIR region. The Co‐MOF exhibited an efficient photothermal effect induced by irradiation with a NIR laser. Under the 808 nm laser (0.7 W cm−2) illumination, the temperature of the Co‐MOF increased from room temperature to 201 °C in only 10 s. Furthermore, a series of polydimethylsiloxane (PDMS) films doped with trace amounts of Co‐MOF showed efficient NIR photothermal conversion. When a Co‐MOF@PDMS (0.6 wt %) film is irradiated by 808 nm laser with power of 0.5 W cm−2, it′s temperature can reach a plateau at 62 °C from 20 °C within 100 s. Our experimental results from the Co‐MOF@PDMS film demonstrate that the effectiveness and feasibility of the material is promising for photothermal applications. The heat is on: A charge‐transfer MOF based on redox‐active TTF/NDI units has been prepared and structurally characterized. Due to the efficient charge‐transfer absorption in the NIR region, the MOF shows excellent photothermal conversion performance. Co‐MOF@PDMS composite films have been studied and could be new candidates for stable and processable materials in photothermal therapy.